Analisis Katalog Perpustakaan Pesantren Darul Hikmah SEI Alim - Alvina, Alvina; Amanda Salsabilla; Widi Puspa Wardani; Yessi Amanda Putri (Jurnal Insan Pengabdian Indonesia, 2025)
Libraries also make an important contribution to the disclosure of information about science which is at the heart of academic life, because with libraries we can obtain data or information that can be used as a basis for the development of science. School/Madrasah libraries are organizations that operate in the service sector. Its main function is to organize, process and disseminate information to readers. Therefore, information needs to be managed (organized). Information organization in the context of a school library, information is the entire collection (printed/electronic) owned by the school library. In library information (collection) organization activities, there are two important activities, namely descriptive cataloging (recognizing the physical collection) and subject indexing/subject analysis (recognizing the contents of the collection). The aim of this collection organization is so that the library's collections are well organized and easy to find again if needed by users and library managers.